Ichnoverruca nom. nov., a replacement name for the genus Verruca Sheng & Sun, 2018 (Hymenoptera, Ichneumonidae) non Schumacher, 1817 - Sheng, Mao-Ling; Jennings, John T. (Zootaxa, 2019)
The name Verruca was proposed for a new genus of wasps described by Sheng & Sun (2018) with the type species Verruca dentia Sheng & Sun, 2018 in the family Ichneumonidae (Hymenoptera). However, it cannot be used as a valid generic name due to homonymy as the genus Verruca was established by Schumacher (1817) in the barnacle family Verrucidae (Cirripedia, Verrucomorpha). Verruca Schumacher is a valid generic name in Verrucomorpha.